(untitled) (Journal on studies and research of academic knowledge, 2018)
The application of biotechnology in the agricultural field aims to enhance the production of certain genetically modified organisms (GMOs) to maximize market yield and resistance through the genetic modification of plants . Its applicability has several disadvantages between them, the environmental consequences producing irreparable damage and the collective and social impact. This work analyses and describes the agrobiotechnology system with soybean cultivation and the adoption of this new model of agriculture in two countries, Argentina and Paraguay. This article was developed according to a generic conceptual structure of agrobiotechnology. It uses bibliographic surveying, collection and interpretation of secondary sources, analysis of bibliographic and data sources.